4-Amino-N-(4,6-dimethylpyrimidin-2-yl)benzenesulfonamide-benzoic acid (1/1) - Arman, H.D.; Kaulgud, T.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The constituents of the title co-crystal, C(12)H(14)N(4)O(2)S center dot C(7)H(6)O(2), are connected by an eight-membered hetero-synthon {center dot center dot center dot NCNH center dot center dot center dot OCOH}, whereby the carboxylic acid forms donor and acceptor hydrogen bonds with a pyrimidine N atom and the adjacent amine, respectively. The dimeric aggregates thus formed are arranged in rows with their terminal NH(2) groups forming N-H center dot center dot center dot O hydrogen bonds with neighbouring aggregates to form a two-dimensional array in the ac plane with an overall T-shaped topology. Layers interdigitate along the b axis being connected by C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi-pi [centroid-centroid distance = 3.6316 (19) angstrom] interactions.